Genotype and phenotype distribution of 435 patients with Charcot–Marie–Tooth disease from central south China. (26th July 2021) - Xie, Yongzhi; Lin, Zhiqiang; Liu, Lei; Li, Xiaobo; Huang, Shunxiang; Zhao, Huadong; Wang, Binghao; Zeng, Sen; Cao, Wanqian; Li, Lu; Zhu, Xiying; Huang, Siwei; et al.
Abstract: Background and purpose: The purpose was to provide an overview of genotype and phenotype distribution in a cohort of patients with Charcot–Marie–Tooth disease (CMT) and related disorders from central south China. Methods: In all, 435 patients were enrolled and detailed clinical data were collected. Multiplex ligation‐dependent probe amplification for PMP22 duplication/deletion and CMT multi‐gene panel sequencing were performed. Whole exome sequencing was further applied in the remaining patients who failed to achieve molecular diagnosis. Results: Among the 435 patients, 216 had CMT1, 14 had hereditary neuropathy with pressure palsies (HNPP), 178 had CMT2, 24 had distal hereditary motor neuropathy (dHMN) and three had hereditary sensory and autonomic neuropathy (HSAN). The overall molecular diagnosis rate was 70%: 75.7% in CMT1, 100% in HNPP, 64.6% in CMT2, 41.7% in dHMN and 33.3% in HSAN. The most common four genotypes accounted for 68.9% of molecular diagnosed patients. Relatively frequent causes were missense changes in PMP22 (4.6%) and SH3TC2 (2.3%) in CMT1; and GDAP1 (5.1%), IGHMBP2 (4.5%) and MORC2 (3.9%) in CMT2. Twenty of 160 detected pathogenic variants and the associated phenotypes have not been previously reported. Broad phenotype spectra were observed in six genes, amongst which the pathogenic variants in BAG3 and SPTLC1 were detected in two sporadic patients presenting with the CMT2 phenotype. Conclusions: Our results provided a unique genotypic and phenotypic landscape of patients with CMT and related disorders from central south China, including a relatively high proportion of CMT2 and lower occurrence of PMP22 duplication. The broad phenotype spectra in certain genes have advanced our understanding of CMT. Abstract : This study provided a unique genotypic and phenotypic landscape of patients with Charcot–Marie–Tooth disease (CMT) and related disorders from central south China, including a relatively high proportion of CMT2 and lower occurrence of PMP22 duplication. The broad phenotype spectra in certain genes, amongst which the pathogenic variants in BAG3 and SPTLC1 related to the CMT2 phenotype, have advanced our understanding of CMT.